Raman phonon modes of zinc blende InxGa1-xN alloy epitaxial layers - Tabata, A.; Leite, JR; Lima, A. P.; Silveira, E.; Lemos, V; Frey, T.; As, D. J.; Schikora, D.; Lischka, K. (American Institute of Physics (AIP), 1999)
Transverse-optical (TO) and longitudinal-optical (LO) phonons of zinc blende InxGa1-xN (0 less than or equal to x less than or equal to 0.31) layers are observed through first-order micro-Raman scattering experiments. The samples are grown by molecular-beam epitaxy on GaAs (001) substrates, and x-ray diffraction measurements are performed to determine the epilayer alloy composition. Both the TO and LO phonons exhibit a one-mode-type behavior, and their frequencies display a linear dependence on the composition. The Raman data reported here are used to predict the A(1) (TO) and E-1 (TO) phonon frequencies of the hexagonal InxGa1-xN alloy. (C) 1999 American Institute of Physics. [S0003-6951(99)01234-6].